Forest community response to invasive pathogens: the case of ash dieback in a British woodland. (22nd February 2016) - Needham, Jessica; Merow, Cory; Butt, Nathalie; Malhi, Yadvinder; Marthews, Toby R.; Morecroft, Michael; McMahon, Sean M.
Summary: Large‐scale mortality events in forests are increasing in frequency and intensity and can lead to both intermediate‐ and long‐term changes in these systems. Specialist pests and pathogens are unique disturbances, as they commonly target individual species that are relatively prevalent in the community. Understanding the consequences of pathogen‐caused mortality requires using sometimes limited available data to create statistical models that can forecast future community states. In the last two decades, ash dieback disease has swept through Europe causing widespread mortality of Fraxinus excelsior L. (European ash) across much of its distribution. In the UK, F. excelsior is an abundant and ecologically important species. Using demographic data from an 18 ha plot in Wytham Woods, Oxfordshire, we built models that forecast the response of this forest plot to the loss of F. excelsior . We combine integral projection models and individual‐based models to link models of growth, survival and fecundity to population dynamics. We demonstrate likely responses in Wytham by comparing projections under different levels of F. excelsior mortality. To extrapolate results to other systems, we test hypotheses regarding the role of abundance, spatial structure and demographic differences between species in determining community response to disease disturbance. We show that the outcome of succession is determined largely by the differing demographic strategies and starting abundances of competing species. Spatial associations between species were shown to have little effect on community dynamics at the spatial scale of this plot. Synthesis . Host‐specific pests and pathogens are an increasingly important type of disturbance. We have developed a framework that makes use of forest inventory data to forecast changes in the population dynamics of remaining species and the consequences for community structure. We use our framework to predict how a typical British woodland will respond to ash dieback disease and show how vital rates, spatial structure and abundance impact the community response to the loss of a key species. Abstract : Host‐specific pests and pathogens are an increasingly important type of disturbance. We have developed a framework that makes use of forest inventory data to forecast changes in the population dynamics of remaining species and the consequences for community structure. We use our framework to predict how a typical British woodland will respond to ash dieback disease and show how vital rates, spatial structure and abundance impact the community response to the loss of a key species.